2022
DOI: 10.1016/j.sapharm.2021.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists and COVID-19 vaccination – Considering mobile phone caller tunes as a novel approach to promote vaccine uptake in low- and middle-income countries

Abstract: As several low- and middle-income countries roll out their COVID-19 vaccination programmes, COVID-19 vaccines hesitancy could threaten the success of such programmes. But pharmacists can play a leading role in addressing COVID-19 vaccine hesitancy by using a critical mobile phone-based technology. This technology, known as caller tunes or ringback tones, is flourishing in low- and middle-income countries such as those in Africa and Asia where it is used to promote popular songs and religious messages. With thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Most people could understand the ringtone because it was played in local languages. A similar strategy has been recommended to replace entertainment and religious ringtones with health promotion, particularly for low and middle-income countries [27]. Our findings also revealed that healthcare providers approached the COVID-19 dashboard and national and international resources for credible sources of information which motivated them to deliver services and enabled vaccination uptake.…”
Section: Discussionmentioning
confidence: 52%
“…Most people could understand the ringtone because it was played in local languages. A similar strategy has been recommended to replace entertainment and religious ringtones with health promotion, particularly for low and middle-income countries [27]. Our findings also revealed that healthcare providers approached the COVID-19 dashboard and national and international resources for credible sources of information which motivated them to deliver services and enabled vaccination uptake.…”
Section: Discussionmentioning
confidence: 52%
“…However, COVID-19 vaccine hesitancy and resistance still haunt governments worldwide ( Du et al, 2021 ; Murphy et al, 2021 ). A growing number of studies have begun to explore effective approaches that overcome the vaccine uptake barrier and promote vaccination rates in the context of COVID-19, such as initiation of beliefs about herd immunity and empathy ( Pfattheicher et al, in press ), mobile phone caller tunes ( Appiah et al, 2021 ), as well as monetary and legal incentives ( Sprengholz et al, 2022 ). Our findings add to the existing work by way of behavioral science insights instead of high-cost monetary incentives and inefficient legal policy.…”
Section: Discussionmentioning
confidence: 99%
“…Unvaccinated health workers who expressed willingness to get vaccinated reported that mobile telephone caller tune messages (heard by a caller after making an outgoing call to another person), international organizations, and the government COVID-19 hotline were the most trustworthy sources of information about COVID-19 and COVID-19 vaccines that could influence their decision to take the vaccine (Figure 2). Somalia, like many other African and Asian countries, replaced the standard ringtone with COVID-19 awareness and prevention messages when the pandemic started [16]. These messages are in Somali, and the Ministry of Health has approved the content.…”
Section: Trusted Sources Of Informationmentioning
confidence: 99%
“…The COVID-19 pandemic caused severe and widespread disruption to essential health services in Somalia, even two years after the first case of COVID-19 was detected in the country on 16 March 2020 [1]. The reasons for this disruption include the lockdown and closure of health facilities because of absenteeism of health care workers who feared getting COVID-19.…”
Section: Introductionmentioning
confidence: 99%